2020
DOI: 10.1371/journal.pcbi.1007653
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of population genomic approaches for mapping colony-level traits

Abstract: Social insect colonies exhibit colony-level phenotypes such as social immunity and task coordination, which are produced by the individual phenotypes. Mapping the genetic basis of such phenotypes requires associating the colony-level phenotype with the genotypes in the colony. In this paper, we examine alternative approaches to DNA extraction, library construction, and sequencing for genome wide association studies (GWAS) of colony-level traits using a population sample of Cataglyphis niger ants. We evaluate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…For instance, for heuristic approaches such as PoolSNP, an exhaustive simulation-based inference for choosing the SNP calling parameters that maximizes the performance of the calling process for specific genomic data can be performed (Kapun et al, 2020). The conclusions drawn from this study could be relevant not only for large-scale population genomics studies but also in cases where the Pool-seq strategy is the only option such as in metagenomic studies and studies with polyploids, among others (Clevenger et al, 2015;Inbar et al, 2020;Pespeni et al, 2013;Shockey et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, for heuristic approaches such as PoolSNP, an exhaustive simulation-based inference for choosing the SNP calling parameters that maximizes the performance of the calling process for specific genomic data can be performed (Kapun et al, 2020). The conclusions drawn from this study could be relevant not only for large-scale population genomics studies but also in cases where the Pool-seq strategy is the only option such as in metagenomic studies and studies with polyploids, among others (Clevenger et al, 2015;Inbar et al, 2020;Pespeni et al, 2013;Shockey et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…More broadly, polygenic traits are difficult to characterize under ideal situations, and so the approach presented here is particularly promising for discrete traits, rare alleles and moderate-to-large effect loci (e.g. [ 17 , 18 , 25 ]). As we continue to identify and validate candidate QTLs, it is conceivable that a gene panel could be developed in white-tailed deer and assist in breeding and management programs or assess the effects of artificial selection by trophy hunting; however, until a reasonable amount of phenotypic variation can be attributed to specific QTL, a gene targeted approach for management and breeding of white-tailed deer will remain a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Coalescent simulations by Hivert et al [ 24 ] showed high accuracy of F ST estimates from pool-seq, at times more precise than individual genomes. Similarly, Inbar et al [ 25 ] showed that pooled approaches produced near identical allele frequency distributions to that of whole and reduced genome sequencing, with simulations reliably detecting moderate to large effect QTL. While Bastide et al [ 26 ] showed that low frequency alleles and small effect sizes, particularly for complex traits, were difficult to detect, this is also the case for non-pooled studies (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…DNA of males collected from a monogynous colony at Lake Henshaw (H-population) in 2019 was used to construct reduced representation genomic libraries following Inbar et al (Inbar et al, 2020), using a modified double-digest (EcoR1 and Mse1) Restriction-site Associated DNA sequencing (ddRADseq) protocol (Parchman et al, 2012; Peterson et al, 2012). Briefly, genomic DNA was digested at 37°C for 8hrs and ligated with uniquely barcoded adaptors.…”
Section: Methodsmentioning
confidence: 99%